Factors influencing minimum acceptable diet (MAD) intake among children aged 6–23 months in remote mid-Himalayan region of Sudurpaschim, Nepal - Basant Kumar Dhami; Dhirendra Nath; Rajendra Lamichhane (BMC Public Health)
Abstract Background Minimum acceptable diet (MAD) intake is crucial for optimizing the growth and development of children aged 6 to 23 months. However, little is known about the factors influencing MAD intake among children of Sudurpaschim. This study, therefore, aims to assess the prevalence of minimum acceptable diet intake and associated factors among children aged 6—23 months in Sudurpaschim Province of Nepal. Methods A cross-sectional study was conducted among mothers of all 404 children aged 6—23 months residing in Malikarjun Rural Municipality, Sudurpaschim Province, Nepal. Data were collected from mothers of children through face-to-face interviews via semi-structured questionnaires. Binary logistic regression was applied to identify the factors associated with MAD intake. Adjusted odds ratios (aOR) with 95% confidence intervals (CIs) were calculated and a p-value < 0.05 was used to determine whether a variable was statistically significant. Results The children were, on average, 16 months old, and over half (55.4%) were male. The prevalence of MAD intake among children aged 6—23 months was 48.5%. Children aged 18 —23 months (aOR: 7.03, 95% CI: 2.29–21.53), mothers with a workload of ≤ 5 hours/day (aOR: 6.52, 95% CI: 2.23–19.03), mothers with sufficient media exposure (aOR: 4.93, 95% CI: 1.99–12.19), and adequate maternal knowledge of complementary feeding (aOR: 16.41, 95% CI: 6.21–43.34) were associated with increased odds of MAD intake. Furthermore, children from families with a monthly income of 151–250 USD (aOR: 16.35, 95% CI: 5.39–49.64), those with > 250 USD (aOR: 16.79, 95% CI: 5.24–53.81), and those from food-secure households (aOR: 8.17, 95% CI: 2.31–28.79) were more likely to receive MAD. Conclusion More than half of the children did not receive MAD. The results indicate an urgent need to increase maternal knowledge of complementary feeding, address socioeconomic disparities, and promote household food security to improve complementary feeding practices.